Organizational And Social Technologies For Early Cancer Detection Among General Population - N. O. Maikova; I. Y. Artyukhin; J. A. Yeremina (Здоровье мегаполиса)
In this review, organizational technologies for early cancer detection including screening programs and patient information management systems are discussed. An analysis of social technologies applied to early cancer detection is carried out, and the role of modern information technologies in cancer control management is discussed. The purpose of the study was to review and analyze existing organizational and social technologies used for early cancer detection, as well as for effectiveness evaluation.